Between Ego(centr)ism and Cooperation: Would People Become Moraly Diseangaged or More Altruistic After the Covid-19 Pandemic? - Frichand, Ana; Donev, Dejan (LIT Verlag GmbH & Co.KG Wien, 2020)
The world is facing great health challenge since COVID-19 pandemic was declared. How- ever, it is not only immense health issue, but also psychological, bioethical, economical, and political one. There are many unanswered questions. Among them is how this pandemic will affect people’s mental health and their moral behavior? In this paper, the authors are focusing on the dilemma whether people will become more morally disengaged, or more altruistic after the pandemic is over. Hence, the knowledge from ethics and psychology is integrated, having in mind that people have potential for being both good and bad in their actions towards others.
Keywords: egocentrism, egoism, cooperation, moral disengagement, altruism, bioethics